Tinjauan Yuridis Putusan Mahkamah Konstitusi Nomor 25/PUU-XIV/2016 dalam Hal Perubahan Ketentuan Pasal 2 dan 3 Undang-Undang Nomor 20 Tahun 2001 tentang Tindak Pidana Korupsi - Angga Alfiyan (PRANATA HUKUM, 2018)
Implementation of the Constitutional Court Decision Number 25 / PUU-XIV / 2016 In the matter of Amendments to the Provisions of Article 2 and 3 of Law Number 20 of 2001 concerning Corruption Crimes and Legal Effects Arising from the Decision of the Constitutional Court Decision Number 25 / PUU-XIV / 2016 in The Amendment to the Provisions of Article 2 and 3 of Law Number 20 of 2001 concerning Corruption. The results of this study are, Opinion of the word "Get" in Article 2 paragraph (1) and Article 3 means "possible", "potential", "can", "not necessarily". If the word "can" is omitted it will weaken Article 2 paragraph (1) and Article 3 of Law Number 31 Year 1999 as amended by Law Number 20 of 2001 concerning Eradication of Corruption, in the case of Corruption categorized as Extraordinary Crime Extraordinary Law law enforcement should be implemented not by weakening the legal basis in eradicating the Corruption.